Effectiveness of the Kalkulating Platform (Stunting Detection Calculator) for Increasing Hemoglobin Levels in Adolescents - Suminar, Ratna; Perdana, Isma Madya; Mulayana, Ridwan; Heriyanti, Silvia Widyani; Hindiarti, Yudita Ingga (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2025)
Background: Anemia in adolescents is one of the contributing risk factors to stunting in early adulthood. Early detection and community-based interventions are essential for promotive and preventive efforts, particularly within school settings. One strategy implemented is the use of the adolescent stunting risk detection feature in the Kalkulating platform, applied by the Youth Information and Counseling Center (PIK R) at SMAN 1 Baregbeg. Objective: This study aimed to determine the effectiveness of the adolescent stunting risk detection feature in reducing anemia cases among adolescents. Methods: This study employed a quantitative descriptive design with a pre-post intervention approach. The subjects were students from SMAN 1 Baregbeg actively engaged in PIK R activities. Hemoglobin (Hb) levels were measured twice by the Baregbeg Public Health Center (Puskesmas Baregbeg), in October 2024 and May 2025. Initially, 44 adolescents were identified with anemia. After interventions including education and routine monitoring using the Kalkulating feature, a follow-up test showed only 10 cases of anemia. Results: There was a reduction of 34 anemia cases from a total of 44, indicating an effectiveness rate of 77.27% and Cohen’s 3,34. According to the effectiveness classification based on percentage change, this intervention falls under the effective category. Conclusion: The implementation of the adolescent stunting risk detection feature in the Kalkulating platform was effective in reducing anemia rates among adolescents. This model can be replicated in school-based health programs with multisectoral support, including primary healthcare providers such as community health centers.